SISTEM INFORMASI HOME SERVICE DAN PENJUALAN SPARE PARTS MENGGUNAKAN MODEL WATERFALL - Subagio, Heri; Masturoh, Siti (Lembaga Penelitian dan Pengabdian Pada Masyarakat, 2024)
Yamaha Karya Laba Motor is a company specializing in motorcycle maintenance and parts sales. Despite its services, shortcomings persist such as verbal vehicle inspections upon service intake and manual recording of service queues and parts sales. Issues arise concerning inventory monitoring, particularly when parts are depleted, necessitating time-consuming manual checks that hinder mechanics' efficiency. Additionally, the lack of home service and online parts sales further complicates customer convenience. The development of a Home Service and online parts sales application at Yamaha Karya Laba Motor aims to address these challenges by enhancing operational efficiency and customer satisfaction. The application includes features such as transaction management, user administration, parts inventory, reporting, Home Service requests, and online parts sales. These functionalities empower Yamaha Karya Laba Motor employees to efficiently monitor parts availability and generate transaction reports. Simultaneously, customers benefit from streamlined processes, saving time and ensuring convenience. This study underscores the transformative impact of digital solutions in improving operational workflows and enhancing service.